School Marketing Practices and Enrollment Interest: Evidence from a Public Primary School in South Sulawesi - Reski Permana, Andi; Ramadani, Wahyu; Rapi, Muh. Taslim; Syamsuriadi, Syamsuriadi (DIDAKTIKA, 2023)
School marketing has become a critical strategy for educational institutions seeking to remain competitive and sustainable, especially in rural and underenrolled schools. This study explores the marketing strategies implemented by SD Inpres 12/79 Walenreng 2, a public elementary school in South Sulawesi, Indonesia, to attract new student enrollment. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis with key school stakeholders, including the principal and homeroom teachers. The findings reveal that the school applies direct socialization strategies, including door-to-door outreach to prospective students' families, as well as basic promotional efforts highlighting the school's mission and character education values. Despite limitations in infrastructure, these efforts demonstrate moderate success in generating interest among prospective students and their families. The study also identifies intrinsic factors (such as curiosity and interest) and extrinsic factors (such as peer influence and parental decisions) that affect student enrollment interest. This research emphasizes the importance of proactive, context-sensitive marketing approaches in educational institutions operating in resource-constrained settings. The findings contribute to a broader understanding of educational marketing in developing country contexts and offer practical insights for school leaders aiming to enhance student recruitment efforts.